A wide-range temperature sensor with a single diode laser based on H2O absorption spectra near 1850.5 nm - Ai, Suman; Xu, Zhenyu; Huang, An; Deng, Hao; Niu, Rantong; Kan, Ruifeng (Frontiers in Physics, 2024)
We have developed a compact sensor utilizing a tunable diode laser near 1850.5 nm to measure H₂O absorption for wide-range temperature diagnostics. The sensor’s performance was experimentally evaluated in a tube furnace at temperatures ranging from 600 to 1800 K and pressures from 3.5 to 103 kPa, showing a relative error between the measured and set temperatures of −2%–3.5%. The numerical simulations confirmed the sensor’s suitability for temperature measurements between 500 and 2500 K, with the accuracy of absorbance extraction being a critical factor. The above results suggest that the sensor is highly effective for temperature measurement across a broad range and holds potential for applications in aerospace and industrial combustion diagnostics.